2020
DOI: 10.1097/crd.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Supraventricular Tachycardia: What the Adult Cardiologist Needs to Know

Abstract: Fetal supraventricular tachycardia management is challenging, with consequences for both the fetus and the mother. If left untreated, fetal hydrops may ensue, at which point delivery and treatment of the arrhythmia is preferred. However, if the fetus is not at term nor near-term, significant doses of antiarrhythmics may be needed to achieve adequate transplacental bioavailability. Although digoxin has classically been the mainstay of treatment, the use of flecainide or sotalol as monotherapy or in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Depending on the medication, antiarrhythmic therapy can cause nausea, vomiting, extreme tiredness, and elevated BNP (brain natriuretic peptide) concentrations. 30,32…”
Section: Role Of the Maternal-fetal Medicine Specialistmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the medication, antiarrhythmic therapy can cause nausea, vomiting, extreme tiredness, and elevated BNP (brain natriuretic peptide) concentrations. 30,32…”
Section: Role Of the Maternal-fetal Medicine Specialistmentioning
confidence: 99%
“…Depending on the medication, antiarrhythmic therapy can cause nausea, vomiting, extreme tiredness, and elevated BNP (brain natriuretic peptide) concentrations. 30,32 Direct monitoring of the fetus for drug toxicity is difficult, although serial Doppler measurements of the atrioventricular interval may demonstrate 10 to 30 milliseconds of prolongation or intermittent AVB. Once drug levels are therapeutic and the fetal heart rhythm is controlled, weekly fetal heart rate monitoring and echocardiograms at 2-to 4-week intervals are suggested.…”
Section: Role Of the Maternal-fetal Medicine Specialistmentioning
confidence: 99%
“…This indicated that sotalol was more efficient in treating fetal atrial fibrillation but less effective for other arrhythmias, especially for the fetus with supraventricular tachycardia, where the fatality rate was higher[ 12 ]. However, Purkayastha et al [ 13 ] pointed out that the management of fetal supraventricular tachycardia with flucanide or sotalol as monotherapy or in combination with digoxin might be the main approach, but this needs to be further evaluated in a practical setting. O'Leary et al [ 14 ] examined 57 cases of fetal persistent tachycardia at 13–37 wk under the control of digoxin, flucanide, sotalol, and amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, amniotic fluid reduction procedures have been necessary. To our knowledge, maternal death from fetal tachyarrhythmia drug treatment has not been reported, but side effects are common and usually well tolerated 30 . These are often specific to the drug and are more common when drugs are given concurrently, in quick succession, or rapidly escalated.…”
Section: Treatment Of Fetal Tachyarrhythmiamentioning
confidence: 99%
“…To our knowledge, maternal death from fetal tachyarrhythmia drug treatment has not been reported, but side effects are common and usually well tolerated. 30 These are often specific to the drug and are more common when drugs are given concurrently, in quick succession, or rapidly escalated. Daily inpatient electrocardiograms and heart monitoring or telemetry are indicated during initiation of drug therapy.…”
Section: Impact Of Fetal Tachycardia Treatment On Maternal and Child ...mentioning
confidence: 99%